Influence of Al2O3 platelets addition on ceramic slurry and local flow induced platelets alignment in ceramic mask stereolithography process. Issue 9 (1st May 2022) - Wu, Xiangquan; Zhang, Zhongming; Ma, Dong; Lu, Xianjiu; Chen, Zhenxian; Gao, Yongchang; Xu, Chunjie
Abstract: Ceramic mask stereolithography can fabricate ceramic parts with complex macrostructures and specific microstructures. Adding the two-dimensional material of alumina platelet crystal to the slurry make this technology possible to print the nacre like "brick-mortar" bionic microstructure ceramics or textured ceramics. However, how the curable ceramic slurry added with the platelets affects the ceramic mask stereolithography process, and how to directly and effectively orient the platelets in the slurry are still needed to be analyzed and solved. This investigation found that without relying on the shear force generated by the slurry scraper, the platelets in the slurry can be directly oriented by the gradient shear stress induced by the local slurry laminar flow during the positioning of the platform. With the increase of the platelets content, the viscosity of the slurries decreased. Since the platelets had fewer scattering effects on ultraviolet light, the increase of the platelets content could increase the curing thickness. In the post-treatment process, compared with the green part without platelets, the shrinkage in the X-Y direction of the green part with oriented platelets was reduced, and the shrinkage in the Z direction was increased. The 50 vol% total solid content slurry with the platelets content of 5 vol% – 20 vol% could be printed through mask stereolithography. The local flow induced alignment effect of the platelets decreased as the solid content of the platelets increased.